Projects of state and political development of muslims in Russia - Bahtiar Fahrutdinov, AidarYurievich Khabutdinov, Marina Maratovna Imasheva,; Milyausha Мuhametzhanovna Khabutdinova, Dina Abdulbarovna Mustafina, Rena Nizamievna Pirov, (Opción, 2019)
The study aims to investigate projects of state and political development of Muslims in Russia at the outset of the 20th century via methods of the analysis and synthesis. As a result, only in the 1990s the edition of works of Muslims of the Russian Empire movement leaders, the edition of the monographs devoted to projects of state and political development of Muslims of Russia at the outset of the 20th century began. In conclusion, the authors disagree with the opinion that showed the movement of Russian Muslims as irredentist and separatist one.